2006
DOI: 10.1016/j.neuropsychologia.2005.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Empathy examined through the neural mechanisms involved in imagining how I feel versus how you feel pain

Abstract: Perspective-taking is a stepping stone to human empathy. When empathizing with another individual, one can imagine how the other perceives the situation and feels as a result. To what extent does imagining the other differs from imagining oneself in similar painful situations? In this functional magnetic resonance imaging experiment, participants were shown pictures of people with their hands or feet in painful or non-painful situations and instructed to imagine and rate the level of pain perceived from differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
507
2
18

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 694 publications
(586 citation statements)
references
References 54 publications
59
507
2
18
Order By: Relevance
“…There is strong evidence from fMRI studies, as well as from lesion studies in neurological patients, that the right temporo-parietal junction plays a critical role for the sense of self-agency (Decety & Sommerville, 2003). It is worth noting that adopting the perspective of another person to imagine his or her emotional reactions (Ruby & Decety, 2004) or to imagine his or her pain (Jackson et al, 2006) was associated with specific increase in Fig. 1.…”
Section: Self-agency and Emotion Regulationmentioning
confidence: 98%
See 1 more Smart Citation
“…There is strong evidence from fMRI studies, as well as from lesion studies in neurological patients, that the right temporo-parietal junction plays a critical role for the sense of self-agency (Decety & Sommerville, 2003). It is worth noting that adopting the perspective of another person to imagine his or her emotional reactions (Ruby & Decety, 2004) or to imagine his or her pain (Jackson et al, 2006) was associated with specific increase in Fig. 1.…”
Section: Self-agency and Emotion Regulationmentioning
confidence: 98%
“…Participants then had to rate the level of perceived pain according to the different perspectives (Jackson, Brunet, Meltzoff, & Decety, 2006). Both the selfand the other perspectives were associated with activation in the neural network involved in pain processing-including the parietal operculum, the ACC, and the anterior insula.…”
Section: Adopting the Perspective Of The Othermentioning
confidence: 99%
“…Empathy is a complex cognitive and emotional skill, generally defined as the ability to subjectively experience the feelings of another person. This ability likely stems from a specific and valid reading of emotional reactions manifested by others [10]. Lack of empathy, as a situational or permanent symptom, appears to be particularly important in sexual offending and psychopathic behaviours.…”
Section: Towards a Brain-computer Interfacementioning
confidence: 99%
“…Moreover, neuroimaging and neurophysiological studies have demonstrated that observing pain in others may activate brain areas similar to those activated when observers experience pain themselves (Jackson, Brunet, Meltzoff, &Decety, 2006;Osborn & Derbyshire, 2010). For example, those who experience vicarious pain (that is, an actual somatosensory experience in response to the observation of pain) show a hyperactivity of motor mirror neurons (enhanced motor-evoked potentials) to the observation of a needle penetrating the hand, relative to the needle having not yet penetrated the hand, as compared with controls (Fitzgibbon, Enticott, Bradshaw, Giummarra, Chou, Georgiou-Karistianis, & Fitzgerald, 2012a).…”
Section: Introductionmentioning
confidence: 99%